Pengujian Aplikasi Pembelajaran Online (E-Learning) Berbasis Web Menggunakan Metode Pengujian Black Box dengan Teknik Equivalence Partitions pada SMK Yayasan Pendidikan Mulia Jakarta - Imam Rifa’i; Hery Fernando; Lukman Nur Prasetya; Faizal Akbar Supriadi; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Application testing is carried out to check whether the program is running properly or there are still errors that need to be corrected so that the program is made into a program that has good quality. In this test, the software that will be tested using a black box with the equivalence partitions technique is the Online Learning Application (E-learning), where this test will focus only on the login form, add admin and teacher forms, and add student forms. This online learning application will be tested to see whether the program is in accordance with the expected function or not without knowing the program code used.